The role of skin biopsy in thje detection of exposure of endocrine disrupting chemicals in mediterranean cetaceans - FOSSI, M. C.; MARSILI, L.; NOTARBARTOLO DI SCIARA, G. (2001)
Here we propose the use of skin biopsy as a sensitive non-lethal technique for the hazard assessment of Mediterranean cetaceans exposed to endocrine disrupting chemicals (EDCs). EDCs have recently attracted much public and scientific attention. They are a structurally diverse group of compounds (including polychlorinated biphenyls, organochlorine pesticides, plasticizers and surfactants) that may adversely affect the health of humans and wildlife, or their progeny, by interaction with the endocrine system. In the Mediterranean environment, top predators accumulate high concentrations of polyhalogenated aromatic hydrocarbons (PHAHs) and toxic metals, incurring high toxicological hazard. In this paper the hypothesis that Mediterranean cetaceans are potentially at risk due to EDCs is investigated using skin biopsy samples. In a project (financed by ICRAM and Italian Ministry of Environment) we used BPMO (MFO) activity in skin biopsies as a potential indicator of exposure to EDCs, such as organochlorines (OCs). Subcutaneous tissue consisting of skin and blubber was obtained from striped dolphins (Stenella coeruleoalba), bottlenose dolphins (Tursiops truncatus), common dolphins (Delphinus delphis) and fin whales (Balaenoptera physalus) in the Mediterranean basin. Sampling was performed in the western Ligurian Sea, between Corsica and the French-Italian coast, and Ionian Sea. High concentrations of DDT metabolites and PCB congeners (known as Endocrine Disruptors) were detected in the different species. Significant differences in BPMO induction and OC levels were found between odontocetes and mysticetes. A statistical correlation was found between BPMO activity and organochlorine levels (op’DDT, pp’DDE) in skin biopsy specimens of the endangered Mediterranean population of common dolphin. These results suggest that BPMO induction may be an early sign of exposure to EDCs such as OCs and a potential warning for transgenerational effects, related to the exposure of future generations via the placenta and milk.